2015
DOI: 10.1145/2783888.2783898
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Filling of Hidden Web Forms

Abstract: A significant part of the information available on the Web is stored in online databases which compose what is known as Hidden Web or Deep Web. In order to access information from the Hidden Web, one must fill an HTML form that is submitted as a query to the underlying database. In recent years, many works have focused on how to automate the process of form filling by creating methods for choosing values to fill the fields in the forms. This is a challenging task since forms may contain fields for which there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Finally, Kantorski et al [47] presented the most recent survey on form filling. Their analysis covers 15 proposals from 2001 to 2013.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, Kantorski et al [47] presented the most recent survey on form filling. Their analysis covers 15 proposals from 2001 to 2013.…”
Section: Related Workmentioning
confidence: 99%
“…Deep Web crawling has a number of applications. The most usual ones are: creating indexed repositories of deep Web pages for search engines [9,25,47] and periodically refreshing the repositories to keep them updated [19,25,71,73], performing automated testing of Web sites [37], or virtual integration, that is, offering a unified view on the data offered by different Web sites [24,87,96].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The public web normally deploys by common use search engine, hidden web represents information, stored in specialized databases, only accessible through specific search interfaces created by using CGI and HTML forms or JavaScript etc. [3] However, a number of recent studies [4,5,6,7] have observed that a significant fraction of Web content in fact lies outside the PIW( Publicly Indexable Web). Specifically, large portions of the Web are "hidden" behind search forms, in searchable structured and unstructured databases (called the hidden Web or deep Web [6]).…”
Section: A Generalitymentioning
confidence: 99%
“…[3] However, a number of recent studies [4,5,6,7] have observed that a significant fraction of Web content in fact lies outside the PIW( Publicly Indexable Web). Specifically, large portions of the Web are "hidden" behind search forms, in searchable structured and unstructured databases (called the hidden Web or deep Web [6]). Pages in the hidden Web are dynamically generated in response to queries submitted via the search forms.…”
Section: A Generalitymentioning
confidence: 99%